A Decision-Making Problem for Selecting an optimal Antivirus Mask over COVID-19 Pandemic under Pythagorean Fuzzy Information Based on Hybrid TODIM - Inferior Ratio Method. Issue 1 (1st May 2022) - Kumar, Sunit; Kumar, Satish
Abstract: Yager was the first who developed the concept of Pythagorean fuzzy sets (PFSs) to tackle uncertainty and vagueness. PFSs is applicable when Intuitionistic fuzzy sets are not able to tackle the uncertainty in real life. In the present paper, based on the concept of Gini-Simpson Entropy, a Pythagorean fuzzy entropy measure is introduced under Pythagorean fuzzy environment. The maximality feature and monotonic behaviour of the developed information measure have been presented to satisfy some elegant mathematical properties which prepare the ground for applications in various disciplines. We extend the TODIM-Inferior ratio method for solving the (MCDM) multicriteria decision-making problems where the behaviour of experts, are taken into consideration. The proposed Pythagorean information measure has been established based on the different cases when weights are partially known. A real-life numerical example has been successfully illustrated to demonstrate the flexibility and efficacy of the developed method.